PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN PENGGUNA KARTU BPJS DI PUSKESMAS KEDAWUNG 1 KABUPATEN SRAGEN - Iin Fajar Wardani (JI@P, 2021)
The research purposes were: 1) determined the effect of tangibles, reliability,responsiveness, assurance, and emphaty on satisfaction of outpatient BPJS cardusers at Puskesmas Kedawung 1, Sragen Regency; and 2) determined the effect ofservice quality on satisfaction of outpatient BPJS card users at PuskesmasKedawung 1, Sragen Regency. This is quantitative descriptive research. Researchwas conducted at Puskesmas Kedawung 1, Sragen Regency. Research sample was50 outpatient who used BPJS cards who checked in August-September 2020 atPuskesmas Kedawung 1. Data collection techniques were used questionnaires,documentation, and literature study. Hypothesis testing were used multipleregression analysis, t test, F test, and coefficient of determination (R2). The resultsshowed that 1) Tangibles, reliability,responsiveness, assurance and empathy havepositive and significant effect on the satisfaction of outpatient BPJS card users atPuskesmas I Kedawung; and 2) Service quality has a positive and significant effecton the satisfaction of outpatient BPJS card users at Puskesmas I Kedawung.Keywords:tangibles, reliability, responsiveness, assurance, empathy, satisfaction